KAJIAN MAKNA PUISI KEAGAMAAN KARYA PENYAIR INDONESIA ANGKATAN ’66 DAN 2000 BERDASARKAN METODE HERMENEUTIKA - Eneng Sri Supriatin (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2019)
This research is based on the background that the development of poetry works cannot be separated from the development of ancient poetry. Poetry is shaped like a poem according to the development of ancient cultural societies that enjoyed language. This is applied in writing written on the stones of the Ka'bah. Then religious poetry appears which will be studied through the hermeneutic method to be used as material for literary appreciation learning. The research objectives are; (1) to find out the meaning of religious poems by Indonesian poet period 66 based on the hermeneutical method; (2) to find out the meaning of religious poems by Indonesian poets period 2000. The research approach used is a qualitative with using descriptive study and literature method. Based on the results of data analysis, it can be concluded that, (1) poetry generation 66 and 2000 contain divine meanings, confession of sins, fear, and servitude to God, and (2) the results of poetry studies with hermeneutical methods can be used as literary appreciation learning. Based on the results of the study, it was suggested that teachers use various approaches to literary work in implementing literary appreciation learning in schools.